An anatomical study of the subcoracoid space (Clinics, 2006)
PURPOSE: To evaluate the amplitude of the subcoracoid space under maximum internal and external rotations of the humeral head and measure the distance between the apex of the coracoid process and the following anatomical structures: (a) point of entry of the musculocutaneous nerve and its branches into the coracobrachial muscles and into the short head of the biceps brachii muscle; (b) acromial artery; (c) lesser tubercle of the humerus. METHOD: Thirty shoulders of fresh cadavers, without any kind of shoulder pathology, (9 males and 6 females) were dissected, and the distances (in mm) were measured between the anatomical structures defined above and the apex of the coracoid process. RESULTS: The mean distance between the apex of the coracoid process and the musculocutaneous nerve was 49.2 mm (in all specimens a proximal branch of the nerve was identified 34.2 mm away from the apex of the coracoid process), which was not significantly different between the sexes or body sides; the mean distance between the apex of the coracoid process and the acromial artery was 12.4 mm, which was not significantly different between the sexes or body sides; the mean distance between the apex of the coracoid process and the lesser tubercle of the humerus, with the humeral head under internal rotation, was 10.6 mm in men and 8.6 mm in women, values that were significantly different between the sexes. DISCUSSION: In women, the smaller distance between the apex of the coracoid process and the lesser tubercle of the humerus in the arm internal rotation suggests a higher chance of impingement between those bone structures among the female sex.